Knowing minds: Linking early perspective taking and later metacognitive insight. (25th October 2020) - Kloo, Daniela; Sodian, Beate; Kristen‐Antonow, Susanne; Kim, Sunae; Paulus, Markus
Abstract : Recent metacognitive research using a partial knowledge task indicates that a firm understanding of 'knowing about knowing' develops surprisingly late, at around 6 years of age. To reveal the mechanisms subserving this development, the partial knowledge task was used in a longitudinal study with 67 children (33 girls) as an outcome measure at 5;9 (years;months). In addition, first‐ and second‐order false belief was assessed at 4;2, 5;0, and 5;9. At 2;6, perspective taking and executive abilities were evaluated. Metacognition at 5;9 was correlated with earlier theory of mind and perspective taking – even when verbal intelligence and executive abilities were partialled out. This highlights the importance of perspective taking for the development of an understanding of one's own mind.